(untitled) (South East Asia Journal of Public Health, 2014)
First year medical students are under severe psychological distress, since they have to cope with the study demands of the medical curriculum. Living away from home and making a transition to a more independent and less supported condition can lead to distress. The present study was designed to determine psychological distress, general self-efficacy and psychosocial adjustments among first year medical college students in New Delhi. A cross-sectional study was designed and data was collected from 88 first year medical students of a government medical college in New Delhi. A pretested, semi-structured questionnaire was administered. The questionnaire consisted of socio-demographic data, Goldbergs General Health Questionnaire (GHQ-12), Schwarzers General Self-efficacy Scale (GSES) and modified Pareeks Pre-adolescent Adjustment Scale (PAAS). According to GHQ-12, 39.7% (95% CI 29.6-50.7) students had psychological distress; it was slightly higher in female students (41.6%) than their male counterparts (38.5%). Psychological distress was greater in students when both of their parents are doctors 66.6% (p-0.016). There was a negative association (r: -0.384) between GHQ-12 scores and GSES scores. From PAAS scores, 19.3% students were found to be maladjusted towards college and 9.1% students were found to be maladjusted with teachers. Adjustment towards peers was found to be good. The prevalence of psychological distress among first year medical students was high. The causes of psychological distress among medical students should be recognized and strategies should be designed to address those issues. DOI: http://dx.doi.org/10.3329/seajph.v3i2.20038 South East Asian Journal of Public Health Vol.3(2) 2013: 35-40